2016
DOI: 10.14407/jrpr.2016.41.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Annual Effective Dose of <sup>210</sup>Po from Sea Food Origin (Oysters and Mussels) in Korea

Abstract: Background: Ingestion of 210 Po laden seafood accounts for a substantial amount of the effective dose of 210 Po. Among seafood items, mollusks, especially domestically produced oysters and mussels, are highly enriched in 210 Po and are consumed in large quantities in Korea. Materials and Methods: Oysters and mussels around the Korean coasts were collected from major farm areas in November 2013. Samples were spiked with an aliquot of 209 Po as a yield tracer, and they were digested with 6 mol•L-1 HNO3 and H2O2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Due to the binding of 210 Po to fish meat, the activity value differed in different fish species which could be due to the difference in habitat, feeding patterns, biological processes, size, season, and other physicochemical elements in the sea. Certain authors correlated the level of 210 Po and 210 Pb in relation to the amount of amino acids, protein and sulfur (Cherrier et al, 1995;Cho et al, 2016;Carvalho et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the binding of 210 Po to fish meat, the activity value differed in different fish species which could be due to the difference in habitat, feeding patterns, biological processes, size, season, and other physicochemical elements in the sea. Certain authors correlated the level of 210 Po and 210 Pb in relation to the amount of amino acids, protein and sulfur (Cherrier et al, 1995;Cho et al, 2016;Carvalho et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Among various radionuclides in the environment, 210 Po and 210 Pb require special attention due to its radiotoxic properties and hyper accumulation potential in marine organisms (Rani et al, 2014;Komperod et al, 2020;Hansen et al, 2022). 210 Po is easily accumulated in fish tissues due to its affinity with proteins when compared to terrestrial foods (Cho et al, 2016). Numerous studies have reported the concentration of 210 Po and 210 Pb in various marine biota around the World (Gouvea et al, 1992;Lubnaet al, 2011;Uddin et al, 2012;Ahmed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The activity value varied in various types of fish due to the binding of 210 Po to fish meat, depending on several factors such as the presence of amino acids, protein (Carvalho et al, 2017), and sulfur (Schwarz, 1976;Cherrier et al, 1995;Church & Sarin, 2007). Water conditions that affect the accumulation of 210 Po in fish include geographic characteristics of habitat, feeding habits, biological processes, fish size, seasonal changes, species, and physical chemistry variables in the sea (Cho et al, 2016). Table 1 shows that the highest 210 Po value occurred in skipjack and ponyfish, with activity concentrations of 207.30 ± 30 Bq/kg (dry wt) and 251.60 ± 2.80 Bq/kg (dry wt), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(a) For the environmental sample in solid state, the digestion step was required. The digestion techniques were classified mainly in two ways including (1) acid digestion (Lin et al, 2009;Cunha et al, 2001;Swift et al, 1998;Ham et al, 1997;Martin et al, 1998;Cho et al, 2016;Prabhath et al, 2015;Sreejith et al, 2014;Jia et al, 2018;Chen et al, 2001; Szarlowicz e a 18 K ç 14 2018; Belivermis et al, 2019; Sanchez-Cabeza e a e a 1998 P aninšek e a 2013; Takizawa et al, 2000;Beals et al, 1989;Sadi et al, 2016) and (2) fusion method Sadi et al, 2016;Maxwell et al, 2019). Acid digestion has been limited to the effect of 210 Po volatilization under different temperature conditions (Martin et al, 1969;Heyraud et al, 1979;Mabuchi et al, 1963;Henricsson et al, 2011;Seiner et al, 2014).…”
Section: Recommended Radiochemical Proceduresmentioning
confidence: 99%